THE CURRENT STATE OF THE LABOR MARKET IN UKRAINE - Babych, Svitlana; Babych, Dmytro (Social Economics, 2018)
The article analyzes the current state and development trends of the Ukrainian labor market taking into account important political and economic events. The unemployment rate, dynamics and structure of the Ukrainian population have been researched in the context of economic activity. The dynamics of the main indicators in the labor market has been determined according to the results of the research of the State Statistics Service according to the methodology of the International Labor Organization. The problems and perspectives of the Ukrainian labor market development have been identified and the measures for its reform have been proposed. In the research have been identified features that affected the formation of the labor market, complicated existing problems in the employment field, and gave rise to new ones. Negative trends have been complicated by regional disproportions in the socio-economic situation. The article lighlights the trends of the main demographic indicators of Ukraine that based on the analysis of the data of the state statistics in the context of the demographic situation and registered migration flows. Migration processes have been analyzed in complex. The reasons and consequences of labor migration have been revealed for Ukraine. Problems of law regulation of labor relations with international migrants and prospects of their solution have been outlined. The problems of the formation of the labor market and its regulation are substantiated, the conclusions and recommendations for increasing the productive employment of the population and law regulation of social and labor relations, that regulate the work activity and determine the social policy in Ukraine, have been worked out.